The new US foreign trade concept - Hubertus Adebahr (Intereconomics, 1973)
On April 10, 1973, the US Administration presented a bill with the ambitious title of “Trade Reform Act”. It has the purpose of equipping the executive with instruments and powers to develop US foreign trade according to its own ideas.
Keywords: 330; USA